Thymic cysts - Anavitarte, E; Filgueira, L; Mendoza, D. (Cirugía del Uruguay, 2020)
Since a case of thymic cyst has been observed, its clinic, radiologic and histopathologic elements are briefly summarized. The small number of cases of this disease is emphasized; a possible embriologic origin is synthetized and the necessary elements to perform a diagnosis of the case of true thymic cyst are exposed.